Capacitance voltage curve simulations for different passivation parameters of dielectric layers on silicon - Sevillano-Bendezu, M. A. (2020)
Surface passivation is a widely used technique to reduce the recombination losses at the semiconductor surface. The passivating layer performance can be mainly characterized by two parameters: The fixed charge density (Q(ox)) and the interface trap density (D-it) which can be extracted from Capacitance-Voltage measurements (CV). In this paper, simulations of High-Frequency Capacitance-Voltage (HF-CV) curves were developed using simulated passivation parameters in order to examine the reliability of measured results. The D-it was modelled by two different sets of functions: First, the sum of Gaussian functions representing different dangling bond types and exponential tails for strained bonds. Second, a simpler U-shape model represented by the sum of exponential tails and a constant value function was employed. These simulations were validated using experimental measurements of a reference sample based on silicon dioxide on crystalline silicon (SiO2/c-Si). Additionally, a fitting process of HF-CV curves was proposed using the simple U-shape D-it model. A relative error of less than 0.4% was found comparing the average values between the approximated and the experimentally extracted D-it's. The constant function of the approximated D-it represents an average of the experimentally extracted D-it for values around the midgap energy where the recombination efficiency is highest.